MODERN APPROACHES TO SERVICE CONDITIONS FACTORS AFFECTING THE HEALTH OF MILITARY SERVICEMEN AND PREVENTION PROBLEMS - Jamshid A. Kutliev; Bobokalon H. Xalimov; Abbos A. Rustamov; Dilafruz, F. Aripova (Web of Journals Publishing, 2024)
This scientific article examined the problems of medical support for troops, as well as service environment factors and prevention issues affecting the health of military personnel, published in national databases, including international databases such as Cyberleninka, Web of Science, PubMed, Medline and Scopus.